Using Video Tutorials to Improve Students' Scalp and Hair Care Skills - Dewi, Siska Miga; Merita, Yanita (UNDIKMA, 2025)
This study aims to determine the effect of using video tutorial media on improving students' skills in performing scalp and hair care. The study used a quasi-experimental method with a one-group pretest-posttest design. The subjects were 32 students of the Make-up and Beauty Study Program who were taking the Scalp and Hair Care course. Data were collected through knowledge tests and practical skills observation sheets, then analyzed using a paired t-test. The results showed an increase in the average score from 62.66 (pretest) to 89.84 (posttest) with a t-value = 13.43 and p < 0.05. Thus, video tutorial media is proven to be effective in improving students' skills in practicing scalp and hair care.